Law Enforcement Against Perpetrators of Criminal Acts In The Insurance Sector In The Perspective of Money Laundering (Study At Manado District Court) - Rahman Amin; Hadrian, Endang; Haryani Putri, Anggreany; Pramudya Tama, Audy (KRTHA BHAYANGKARA, 2024)
Human life activities are inseparable from the risks that can occur at any time that can cause losses. One effort to overcome this is to use insurance services, but today there are often cases of insurance that harm the community, among others, due to irregularities by insurance agents and the perpetrators are only subject to criminal sanctions in the insurance sector, even though the act is a criminal act of money laundering. This research is a normative juridical research, using a statutory approach and a case approach. The results of the study, that law enforcement against perpetrators of criminal acts in the insurance sector in the perspective of money laundering in cases committed by Mrs. Swita Glorite Supit based on Manado District Court Decision Number: 125/Pid.Sus/2021/PN. Mnd dated June 8, 2021, has not been implemented optimally in accordance with the provisions of applicable laws and regulations, where law enforcement only applies the provisions of general crimes and criminal acts in the insurance sector, despite the fact that Mrs. Swita Glorite Supit committed money laundering proceeds in the insurance sector. Obstacles in law enforcement against perpetrators of criminal acts in the insurance sector in the perspective of money laundering in cases committed by Mrs. Swita Glorite Supit, consists of aspects of legal substance, where the provisions on criminal acts in the field of insurance and money laundering are special crimes so that Investigators and Public Prosecutors only apply crimes in the field of insurance, and there are no regulations of the Financial Services Authority that specifically regulate the procedures, procedures and activities of insurance agents. Aspects of legal structure, where the understanding of law enforcement who handles the case so that it does not apply the provisions of money laundering in accordance with the actions committed by Mrs. Swita Glorite Supit, and aspects of legal culture, where the public does not know and understand well the provisions governing criminal acts in the field of insurance, and about money laundering